A Marxist theory of ideology : praxis, thought and the social world - Sau, Andrea, 1988- (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This work explores the question of defining ideology from a Marxist perspective. Advancing beyond the schemas of discussion presented in current Marxist literature, the author offers an account of how the concept of ideology should be defined and what role it plays within historical materialism. Through a close reading of Marx's relevant writings, this volume demonstrates that while there is no coherent, single account of ideology in Marx's work, his materialist framework can be reconstructed in a defensible and 'non-deterministic' way. The definition of ideology presented is then articulated through a close reading of Gramsci's Prison Notebooks. Efforts are also made to demonstrate that Gramsci's interpretation of historical materialism is indeed consistent and compatible with Marx's. A systematic articulation of a theory of ideology that combines the works of Marx and Gramsci, as well as adding elements of Bourdieu's social theory and William James's psychology, this volume will appeal to scholars of social and political theory with interests in political economy and Marxist thought"--
OCLC-licensed vendor bibliographic record.
Keywords: Marx, Karl, -- 1818-1883.; Ideology; Communism; Socialism; Philosophy, Marxist; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General